2010
DOI: 10.1007/s11743-010-1223-6
|View full text |Cite
|
Sign up to set email alerts
|

Phase and Rheological Behavior of Cetyldimethylbenzylammonium Salicylate (CDBAS) and Water

Abstract: The temperature-composition phase diagram in the diluted region of the cationic surfactant cetyldimethylbenzylammonium salicylate/water system was studied with a battery of techniques. The Krafft temperature (T k = 33 ± 1°C) was measured by differential scanning calorimetry, polarizing microscopy, conductimetry, viscosimetry, and rheometry. The critical vesicle concentration (cvc, *0.002 wt%) and a vesicle-micellar transition (cvm, *0.005 wt%) was detected at a temperature of 35°C. Below T k and concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 76 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…Hydrotropes cannot form organized self-associated structures, such as micelles, because their hydrophobicity is lower than that of surfactants; however, they decrease substantially the critical micellar concentration (cmc) and induce the transition from spherical to rod micelles (cmc 2 ) as well as wormlike micelles formation at lower surfactant concentrations. This ability typically increases when the hydrotrope molecules have aromatic structures [3][4][5][6][7][8][9][10][11][12][13][14][15]. For instance, the addition of hydrotrope salts such as 2-hydroxybenzoate to cetyltrimethylammonium bromide (CTAB) solutions induces the formation of wormlike micelles at very low concentration whereas the addition of 3-and 4-hydroxybenzoate counterions does not.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrotropes cannot form organized self-associated structures, such as micelles, because their hydrophobicity is lower than that of surfactants; however, they decrease substantially the critical micellar concentration (cmc) and induce the transition from spherical to rod micelles (cmc 2 ) as well as wormlike micelles formation at lower surfactant concentrations. This ability typically increases when the hydrotrope molecules have aromatic structures [3][4][5][6][7][8][9][10][11][12][13][14][15]. For instance, the addition of hydrotrope salts such as 2-hydroxybenzoate to cetyltrimethylammonium bromide (CTAB) solutions induces the formation of wormlike micelles at very low concentration whereas the addition of 3-and 4-hydroxybenzoate counterions does not.…”
Section: Introductionmentioning
confidence: 99%
“…This research concluded that micellar solutions composed of cationic surfactants at concentrations close to the CMC show Newtonian behavior [4]. However, with increasing surfactant concentration, distinct phase structures with viscoelastic properties are observed, indicating network formation [17]. The rheological and mechanical properties of surfactant solutions depend on the network which is formed by the self-associating molecules interacting among themselves [1,2].…”
Section: Introductionmentioning
confidence: 94%
“…Hydrotropes can also induce the formation of wormlike (polymer-like) micelles at lower surfactant concentrations. This ability is larger when the hydrotrope counterions possess benzene derivative structures [3][4][5][6][7][8][9][10][11][12]. As an example, when 4-(4CB ? )…”
Section: Introductionmentioning
confidence: 99%
“…Electronic supplementary material The online version of this article (doi:10.1007/s11743-017-1934-z) contains supplementary material, which is available to authorized users. 4-hydroxybenzoate (4HB ? ) hydrotropic counterions are incorporated, wormlike micelles are not formed [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation